Analysis of pathogenic bacteria and antimicrobial susceptibility with burn and various wounds from 2019 to 2021 - Liu Yanxin, Zhang Wei, Chen Huaxia (Xin yixue, 2022)
Objective To analyze the sensitivity of common pathogens and common antibiotics in burn and wound repair surgery patients, aiming to provide reference for the prevention and treatment of burn and various wounds. Methods From March 2019 to March 2021, 310 bacterial culture specimens of wound secretion from burn and wound repair surgery patients with suspected wound infection were collected. VITEK 2 Compact automatic bacterial identification instrument and VITEK MS automatic rapid microbial mass spectrometry detection system were used for pathogen identification. Disk diffusion method and instrumental method were employed to detect the antimicrobial susceptibility. The drug resistance of pathogens was analyzed by WHONET 5.6 software. Results Among 310 samples, 179 positive samples were detected, with a positive rate of 57.74%, 84 cases of Gram-positive bacteria, accounting for 46.93%, 91 cases of Gram-negative bacteria, accounting for 50.84% and 4 cases of fungi, accounting for 2.23%. Among them, Gram-negative bacteria were Pseudomonas aeruginosa （PAE）, Acinetobacter baumannii （ABA）, Klebsiella pneumoniae （KPN） and Escherichia coli （ECO）. Staphylococcus aureus （SAU） was the main Gram-positive bacteria. Among the detected Gram-negative bacteria, the sensitivity rate of PAE to polymyxin B, myxin and amikacin was more than 80.40%. The sensitivity rate of ABA to myxin, polymyxin B and tegacyclin exceeded 96.70%. The sensitivity rate of KPN to tegacyclin and polymyxin B antibiotics was higher than 88.90%. The sensitivity rate of ECO to cefotetan, amikacin, piperacillin/tazobactam and carbapenem antibiotics was >92.90%. Among the detected Gram-positive bacteria, the sensitivity of SAU to linezolid, vancomycin and tetracycline was up to 100.00%, and that of Enterococcus to tetracycline, vancomycin and linezolid was also 100.00%. Conclusions Gram-negative bacteria are the main pathogens in patients with wound infection from Department of Burn and Wound Repair Surgery. Antibiotic susceptibility rate of these bacteria were different. Necessary attention should be paid to these pathogens. During the treatment of infection, clinicians should cultivate and prepare bacterial specimens for accurate examination before selecting antibiotics. According to the results of drug sensitivity, they should choose proper antibiotics, and adopt definite treatment instead of empirical medication as early as possible, aiming to inhibit the generation of drug-resistant strains and improve the effectiveness of antibiotic treatment.